Hypercalcemia: A Practice Overview of Its Diagnosis and Causes - Vincenzo Calabrese; Roberta M. Messina; Valeria Cernaro; Alessandra Farina; Ylenia Di Pietro; Guido Gembillo; Elisa Longhitano; Chiara Casuscelli; Giovanni Taverna; Domenico Santoro (Kidney and Dialysis)
Hypercalcemia is defined as a serum calcium concentration higher than 10.5 mg/gL or 2.6 mmol/L. Only 50% of serum calcium is active, presented as ionized calcium. The remaining half is bound to albumin, phosphate, and other serum anions, and their changes can affect the serum calcium concentration. Thus, to discriminate true hypercalcemia from pseudo hypercalcemia, an ionized calcium concentration higher than 1.3 mmol/L might be more appropriate. Many variables can lead to hypercalcemia, and managing them is necessary to treat this ion disorder. Indeed, it can be caused by malignancies, hematologic disorders, or genetic diseases such as familial hypocalciuric hypercalcemia, or it can be related to hormone disorders involving parathormone or vitamin D. For this condition, the correct diagnostic algorithm should be followed. In this review, we summarize the diagnostic steps to follow and detail each clinical pathway is involved in hypercalcemia.